PERAN ORANG TUA DALAM MEMOTIVASI BELAJAR ANAK STUDY FROM HOME (SFH) SEBAGAI UPAYA MEMUTUS PENULARAN CORONAVIRUS DISEASE - Khaidir Fadil; Amran Amran; Noor Isna Alfaien; Indah Oktaviani (Universitas Pasundan, 2022)
This study is a literature review with the aim of knowing the critical involvement of parents in encouraging children to study at home in an effort to break the chain of transmission of the Coronavirus disease. This study was conducted in six stages: selection of study subjects, literature review, literature reduction, organizing literature, literature review, and drawing conclusions. Sources of data used are secondary data sources. Data and information retrieval was obtained using documentation techniques such as finding more relevant data from various sources including e-books, study journals, scientific articles, news, and other study-related documents. The findings of this study indicate that parents play an essential role in their children's learning process at home, especially in providing education and motivation to children to continue learning in the midst of the current Coronavirus disease outbreak.